A Systematic Review of Student Disability and Race Representation in Universal School-Based Social and Emotional Learning Interventions for Elementary School Students. (February 2023) - Cipriano, Christina; Naples, Lauren H.; Eveleigh, Abigail; Cook, Amanda; Funaro, Melissa; Cassidy, Colleen; McCarthy, Michael F.; Rappolt-Schlichtmann, Gabrielle
The authors present a systematic review of elementary school universal school-based (USB) social and emotional learning (SEL) interventions from 2008 through 2020 for two groups of minoritized students in education research and practice: students with disabilities and/or minoritized racial identities. Completed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards, in this review the authors identified 269 studies for inclusion, which reflected 107 USB SEL interventions. Eleven studies explicitly excluded students with disabilities. Studies varied widely in how disability and racial identity were categorized within and across studies and provided limited evidence of effectiveness through the use of subgroup analyses to support meaningful assessment of how students with disabilities and racially minoritized elementary school age students are benefiting from USB SEL interventions. The authors discuss the limitations of findings, education research best practices, and the minimum reporting standards necessary to ensure ability and racially minoritized youth representation in future USB SEL research.